DAMPAK KREDIT PT PNM MEKAAR TERHADAP KINERJA USAHA ULTRA MIKRO DI KECAMATAN BATU - Mayangsari, Bunga Adelia; Zuhroh, Idah; Hadi, Syamsul (Journal of Financial Economics & Investment, 2021)
This study aims to analyze the performance of ultra micro businesses after obtaining venture capital financing from PT. Permodalan Nasional Madani (PNM). Judging from the performance and impact felt by ultra micro entrepreneurs in Batu District, after receiving financing from PT. PNM. This study uses primary data, with a simple regression analysis tool. The results showed that the financing program from PNM Mekaar had an impact on increasing capital, increasing turnover, increasing operating profits and increasing assets. However, this does not affect the increase in the workforce and the increase in business branches of ultra micro entrepreneurs in Batu District.